Ultrasonographic Evaluation of Effects of Pregnancy on Thyroid Volume in a Nigerian Cohort - , Enighe W Ugboma; , Chidinma Wekhe (Archives of Current Research International, 2024)
Background: During pregnancy, the thyroid gland experiences physiological changes critical for metabolism regulation. Ultrasonography provides a non-invasive means to assess these changes effectively. Thyroid gland responds physiologically to increased demands for iodine and energy which is the case in pregnant women. Aim: This study aims to evaluate the physiological and pathological alterations in the thyroid gland of pregnant women across gestational ages (0-40 weeks) at a specialist hospital in Port Harcourt, Nigeria. The study is also aimed at giving normative values of thyroid volume in pregnancy which helps in ascertaining when a pregnant woman develops goiter as well as properly monitor thyroid hormones. Methods: A prospective study involving 559 healthy pregnant women was conducted from September 2023 to May 2024. Data collected included age, BMI, weight, and height. Thyroid volume was assessed via ultrasound. Statistical analysis was performed using SPSS version 21.0 with a significance level set at p < 0.05. Results: The mean maternal age was 29.95 ± 6.34 years. Significant positive correlations were observed between thyroid volume in the right lobe and variables such as age, BMI, weight, and height. The left lobe volume showed a positive correlation with parity. Conclusion: The study confirms thyroid volume increases during pregnancy, with significant correlations to specific demographic and anthropometric factors. These findings underscore the importance of routine ultrasonographic evaluation of the thyroid in pregnant women for early detection and management of potential disorders.